PENGARUH OPENESS TO EXPERIENCE DAN CONSCIENTIOUSNESS TERHADAP PERILAKU KERJA KONTRAPRODUKTIF(STUDI PADA PEGAWAI NEGERI SIPIL DI UIN MATARAM) - Eva Yanuartha (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at analysis the effect of personality openness to experience and conscientiousness on the counterproductivebehavior of civil servant State Islamic University UIN Mataram. The data were collected by using questionnaires, interviews anddocumentation. The population is all 104 civil servants of UIN Mataram.The data analysis was using multiple regressions.The research showed that openness to experience and conscientiousness had negative and significant effect on the harmful behavior. It is suggested that personality openness to experience and conscientiousness be improved in order the counterproductive behavior could be decreased. In addition, UIN Mataram needs to provide appropriate working environment for employees in order that good behavior is maintained and improved. The management of UIN Mataram needs to apply the good leadership function in terms of assertiveness and justice. UIN Mataram needs to provide trainings for staffs of civil servants evenly to improve the competence for new jobs. UIN Mataram needs to provide fair job and rotate the staff every two to three years in order that employees/ civil servants face challenges in the new position and to have concern for the institution. Keywords: openness to experience, conscientiousness, unproductive behavior